The Strategic Role of Higher Education Management in Enhancing the Quality of Learning and the Welfare of Lecturers and Staff - M. Sahidi (Journal of Scientific Studies and Multidisciplinary Research, 2026)
Higher education institutions are increasingly required to enhance the quality of learning while ensuring the welfare of lecturers and staff in response to global academic and organizational challenges. This study aims to analyze the strategic role of higher education management in improving learning quality, examine its relationship with the welfare of lecturers and staff, and develop an integrated theoretical framework that connects these variables. This research employed a qualitative approach using a theoretical research design based on a systematic literature review. Data were collected from peer-reviewed journal articles, academic books, and relevant scholarly publications published between 2015 and 2025. The data were analyzed using qualitative content analysis and thematic analysis to identify key patterns, relationships, and conceptual gaps. The findings reveal that higher education management contributes significantly to learning quality through strategic planning, lecturer performance management, leadership, and quality assurance systems. Additionally, lecturer and staff welfare is strongly influenced by human resource management policies, compensation systems, work environments, and psychological well-being. Importantly, this study finds that an integrated management approach that aligns strategic management, human resource development, and welfare policies creates a mutually reinforcing system that enhances both academic quality and welfare simultaneously. In conclusion, this study highlights the importance of adopting a holistic and sustainable management approach in higher education to achieve academic excellence and human well-being, providing both theoretical contributions and practical implications for policymakers and institutional leaders.